Myeloperoxydase and CD15 With Glycophorin C Double Staining in the Evaluation of Skin Wound Vitality in Forensic Practice - Gauchotte, Guillaume; Bochnakian, Agathe; Campoli, Philippe; Lardenois, Emilie; Brix, Muriel; Simon, Etienne; Colomb, Sophie; Martrille, Laurent; Peyron, Pierre-Antoine (Frontiers in Medicine, 2022)
Background: The determination of skin wound vitality based on tissue sections is a challenge for the forensic pathologist. Histology is still the gold standard, despite its low sensitivity. Immunohistochemistry could allow to obtain a higher sensitivity. Upon the candidate markers, CD15 and myeloperoxidase (MPO) may allow to early detect polymorphonuclear neutrophils (PMN). The aim of this study was to evaluate the sensitivity and the specificity of CD15 and MPO, with glycophorin C co-staining, compared to standard histology, in a series of medicolegal autopsies, and in a human model of recent wounds. Methods: Twenty-four deceased individuals with at least one recent open skin wound were included. For each corpse, a post-mortem wound was performed in an uninjured skin area. At autopsy, a skin sample from the margins of each wound and skin controls were collected (n=72). Additionally, the cutaneous surgical margins of abdominoplasty specimens were sampled as a model of early intravital stab wound injury (scalpel blade), associated with post-devascularization wounds (n=39). MPO / glycophorin C and CD15 / glycophorin C immunohistochemical double staining was performed. The number of MPO and CD15 positive cells per 10 high power fields (HPF) was evaluated, excluding glycophorin C – positive areas. Results: With a threshold of at least 4 PMN /10 high power fields, the sensitivity and specificity of the PMN count for the diagnostic of vitality were 16% and 100%, respectively. With MPO / glycophorin C as well as CD15 / glycophorin C IHC, the number of positive cells was significantly higher in vital than in non-vital wounds (p<0.001). With a threshold of at least 4 positive cells / 10 HPF, the sensitivity and specificity of CD15 immunohistochemistry were 53% and 100%, respectively; with the same threshold, MPO sensitivity and specificity were 28% and 95%. Conclusions: We showed that combined MPO or CD15 / glycophorin C double staining is an interesting and original method to detect early vital reaction. CD15 allowed to obtain a higher, albeit still limited, sensitivity, with a high specificity. Confirmation studies in independent and larger cohorts are still needed to confirm its accuracy in forensic pathology.